Exploring the intention of Malaysian to adopt green investment - Chow, Khe Xing; Oh, Hui Ying; Tan, Sean Shao En; Wong, Kit Yeng (2025)
As environmental concerns intensify globally, the concept of green finance has gained significant attention as a means to promote sustainable investment practices. This study investigates Malaysians’ desire to make green investment with the goal of identifying the variables that affect their propensity to use sustainable financial products. Green investment, which focus on environmentally responsible projects, have the potential to play a key role in addressing climate change and fostering economic sustainability. The main goal of this research is to determine the factors that shape Malaysians’ perceptions and intentions about green investment. Specifically, the study examines how factors such as environmental concern, perceived behavioural control, subjective norms and attitude towards green influence individuals’ investment decisions. A quantitative approach was employed, using a survey distributed to a diverse sample of 384 Malaysian citizens. The Statistical Package for the Social Sciences (SPSS) version 30.0 was employed for the data analysis. The results show that worries about the financial returns of green financial products and a lack of knowledge about them continue to be major obstacles. This study provides valuable insights into the adoption of green finance in Malaysia, suggesting ways for policymakers and financial institutions to increase public engagement with sustainable investment practices. By improving education, policy incentives and access to green financial products, Malaysia can strengthen its transition towards a more sustainable and zero net emission country.